Preparation and properties of oriented sorghum-thermoplastic composites using flat hot-pressing technology. (August 2015) - Qi, Chusheng; Yadama, Vikram; Guo, Kangquan; Wolcott, Michael P
In order to increase the value of sorghum for bioethanol products, a new method of fabricating oriented sorghum fiber and high-density polyethylene composites (OFPC) using flat hot-pressing technology is presented in this study. The effect of high-density polyethylene (HDPE) loading (0, 10, 20, 30, 40 wt %) on the physical and mechanical properties of OFPC was analyzed. In addition, the mat compression properties, vertical density profile, and microscopic structure of the resulting OFPC were examined. Improvement in mechanical and physical properties of OFPC was observed when 10% HDPE was included with sorghum fiber in the composites. HDPE loading greater than 10% did not further enhance the mechanical properties of OFPC, but improved their water resistance ability. Lower consolidation pressure was required to condense the composite mats with higher HDPE loadings during the hot pressing process. The density distribution of OFPC was greatly improved by the addition of HDPE, but larger density fluctuation was observed at higher HDPE loading.